Standard handbook of biomedical engineering and design (McGraw-Hill, 2003)
The Standard Handbook of Biomedical Engineering bridges the gap between engineering principles and biological systems. Over 40 experts from universities and medical centers throughout North America and Israel have produced a practical reference for the biomedical professional who is seeking to solve a wide range of engineering and design problems, whether to enhance a diagnostic or therapeutic technique, reduce the cost of manufacturing a medical instrument or prosthetic device, improve the daily life of a patient with a disability, or increase the effectiveness of a hospital department.